The Implementation of the Pancasila Economy to Empower MSMEs Post Pandemic Covid 19 - Suyanto (JURNAL PUSAKA, 2022)
Many industries have been affected by the COVID-19 outbreak, especially the economy. This economic impact is not only felt locally but even internationally. The marketing plan for MSMEs engaged in the creative economy sector, namely human activities in which individuals independently manage economic resources while being under the authority they control. MSMEs are currently changing their marketing tactics to advertise their products through online marketplaces in the era of globalization. To find out how a Pancasila-based economy that is transitioning to the digital era will be used and how local government priorities for MSMEs during a pandemic are the goals of this research. A literature study approach is used in this article to describe various books, journals, and internet publications. The study of the findings of this article shows that the growth of digital MSMEs and digital entrepreneurship in Indonesia amid the Covid pandemic has turned into a rescue solution. One of the solutions to ensure that MSMEs remain accessible during the Covid 19 pandemic is the establishment of digital MSMEs. Various MSME digitalization development projects in the Indonesian Pancasila digital economic ecosystem can accelerate the digital transformation process. During the Covid 19 outbreak, the creative economy sector adhered to a Pancasila-based economic system, and supporting elements for entrepreneurship included promotions, excellent service, customer appreciation, affiliation or partnerships, and social capital. keywords: digitalization; economy; globalization; pandemic; MSME